Development of Smart IOT Based Power Adapter - Attappan, Arun A/L; Lukose, Jacqueline; Magaswaran, Kumaresan A/L (Journal of Applied Technology and Innovation, 2020)
The main aim of this research is to develop Smart IOT based Power Adapter. In this proposed method, a Smart Power Adapter was developed along with the BLYNK mobile application to control and monitor the electrical power consumption. The performance of the developed smart power adapter is evaluated by testing the accuracy of power consumption for each home appliances, Battery capacity testing, cost of power consumed data for different home appliances, Cost saving with smart power adapter features and without features. Finally, the testing on changing the voltage sensor value for most prominent value for power consumption. It is observed that the approach for calculating the power consumed by home appliances shows least error of 0.1%. Where else, the battery power back up on the adapter only provide 5 hours of continues power usage. Besides that, the wireless control over the power adapter works flawless along the time scheduling. Finally, the smart power adapter estimates the costing of the power consumption relying on the usage of electrical power with least components.